Enhancing the melting rate of RT42 paraffin wax in a square cell with varied copper fin lengths and orientations: A numerical simulation - Saif Ali Kadhim; Karrar A. Hammoodi; Mohammed J. Alshukri; Issa Omle; Karrar K. Abdul Hussein; Abbas Fadhil Khalaf; Ammar Elsheikh (International Journal of Thermofluids)
Latent thermal energy storage units are especially preferred in renewable thermal energy systems for their significant capacity to store heat. Nevertheless, the phase change materials in these units have low thermal conductivity, prompting researchers to tackle this problem using several methods, such as incorporating fins. This numerical study contributes to improving the charging rate of a square cell (50 × 50 mm) used paraffin wax RT42 as phase change material by adding 4 copper fins inside, 1 mm thick and of different lengths. The fins were positioned on the left wall, where a constant-temperature heat flux was applied, while the other walls were thermally insulated. Four configurations of the cell were examined: without fins, with 10 mm length fins, with 20 mm length fins, and with 30 mm length fins, respectively. The results demonstrated that the presence of fins significantly improved the charging rate of the square cell. Compared to the baseline configuration without fins, the time required for the paraffin wax RT42 to completely melt was reduced by 22.22 %, 33.33 %, and 55.56 % with fins of 10 mm, 20 mm, and 30 mm lengths, respectively. Configuration four was also compared with a setup where similar fins were positioned on the bottom wall while maintaining the heat flux on the left wall. It was observed that the total melting time doubled compared to configuration four, suggesting that the optimal placement for the heat flux is on the wall where the fins are located. The study contributes to enhancing and developing the charge rates of square and rectangular PCM cells such as these used for cooling PV panels.